Semi Automatic T-Shirt Folding Machine Berbasis PID (Proportional Integral Derivative) - Apriliyanto, Muhammad; Ulum, Miftachul; Joni, Koko (J-Eltrik, 2020)
The process of folding clothes is one of the activities carried out in the laundry business or household. The activity is fairly easy but many people are still lazy to do it. As a result, clothes that have been washed will fall apart in certain rooms, thereby reducing the aesthetic value of a home. Semi Automatic T-Shirt Folding Machine is the right solution to make folding clothes easier and more time efficient. This tool is equipped with a servo motor that moves the folding board that has been designed in such a way that the user only needs to manghandle the shirt just once and simply push one button then the shirt will fold itself and will be neatly arranged through the clothes stacker board. The PID method is applied to DC motors that move under the clothes folder so that the buildup of clothes underneath will not be pressured upward when the clothes are piled up when they are folded. Ultrasonic sensor will measure the right height between the clothes with the door opening the stacking clothes with kp = 1, ki = 0.1, kd = 0.5 for thin clothes and kp = 5, ki = 1, kd = 2.5 for thick clothes so that the movement of the motor can adjust its speed . This tool can fold one shirt in 16.83 seconds 11 seconds faster than folding clothes manually